Impact of COVID-19 on vaccine confidence and uptake: A systematic literature review - Ivo Vojtek; Marloes van Wouw; Angus Thomson (Taylor & Francis Group, 2024)
During the coronavirus disease 2019 (COVID-19) pandemic, scheduled vaccinations were postponed, mass vaccination programmes were suspended and opportunities for healthcare workers to administer vaccines ad hoc decreased. The aims of this systematic literature review were to determine the impact of the COVID-19 pandemic on vaccine confidence, intent and uptake in preexisting routine childhood or adult vaccination programmes, and to identify factors associated with changes in acceptance, intent and uptake of preexisting vaccines. Medline and Embase were searched for studies in Australia, Brazil, Canada, China, Japan, the USA, and European countries, published between 1 January 2021 and 4 August 2022. A complementary gray literature search was conducted between 11 and 13 October 2022, and supplemented with additional gray research in October 2023. In total, 54 citations were included in the review. Study design and geography were heterogeneous. The number of adults who received or intended to receive an influenza or pneumococcal vaccine was higher during the pandemic than in previous seasons (n = 28 studies). In addition, increased acceptance of adult vaccinations was observed during 2020-21 compared with 2019-20 (n = 12 studies). The rates of childhood vaccinations decreased during the COVID-19 pandemic across several countries (n = 11 studies). Factors associated with changes in intention to receive a vaccination, or uptake of influenza vaccine, included previous vaccination, older age, higher perceived risk of contracting COVID-19, anxiety regarding the pandemic and fear of contracting COVID-19. Acceptance and uptake of influenza and pneumococcal vaccines generally increased after onset of the COVID-19 pandemic.